TThe impact of smart human resource management practices on Sustainable performance mediated by job satisfaction: an analytical study in Ministry of Education - Al- Diwaniyah Education Directoratehe impact of smart human resource management practices on Sustainable performance mediated by job satisfaction: an analytical study in Ministry of Education - Al- Diwaniyah Education Directorate (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to explore the relationship between smart human resource management (HRM) practices and sustainable performance in the selected organizations, with a specific focus on the mediating role of job satisfaction. In today's highly competitive and constantly changing work environment, achieving sustainable employee performance has become a top priority for organizations. Smart HRM practices, which leverage modern technologies and data analytics for informed decision-making, are considered a promising approach to enhancing human resource effectiveness. It is believed that these practices not only directly impact employee performance but also contribute to an increase in job satisfaction, which plays a crucial role in motivating employees toward higher performance. In this study, we will shed light on how the interplay between these three variables and their dimensions affects the success of organizations in achieving their strategic goals. To arrive at tangible results, a descriptive-analytical methodology was used to present and interpret the study's information. A questionnaire was also employed as the main tool for data collection to achieve the study's objectives, in addition to conducting personal interviews. The study's population consisted of all employees (staff and managers) in the human resources departments of the selected organizations, totaling (235) employees. Questionnaires were distributed to all employees and all were returned, with (231) valid questionnaires representing the study's sample. The results of the statistical analysis concluded with several key findings, the most prominent of which is the existence of a statistically significant effect of smart HRM practices on sustainable performance. This indicates that smart HRM practices have a significant and influential role in achieving sustainable employee performance. In other words, the more educational institutions strive to effectively implement smart HRM practices, the more it will serve as a key factor in achieving sustainable performance levels and job satisfaction.
Keywords: Smart Human Resources Management (HRM) Practices; Sustainable Performance; Job Satisfaction; AL-Diwaniyah Education Directorate